Isolation of Japanese encephalitis virus from mosquitoes collected in Sabak Bernam, Selangor, Malaysia in 1992 - Vythilingam, I.; Oda, K.; Chew, T.K.; Mahadevan, S.; Vijayamalar, B.; Morita, K.; Tsuchie, H.; Igarashi, A. (1995)
Detection and isolation of Japanese encephalitis (JE) virus were attempted from female mosquitoes collected in Kampong Pasir Panjang, Sabak Bernam, Selangor, from May to November 1992. A total of 7,400 mosquitoes consisting of 12 species in 148 pools were processed and inoculated into Aedes albopictus clone C6/36 cell cultures. Of these, 26 pools showed the presence of viral antigens in the infected C6/36 cells by specific immunoperoxidase staining using an anti-JE virus polyclonal antibody. Presence of JE virus genome was confirmed in the infected culture fluid for 16 pools by using reverse transcriptase-polymerase chain reaction and JE virus-specific primers. Of these, 3 pools were from Culex tritaeniorhynchus, 4 from Culex vishnui, 3 from Culex bitaeniorhynchus, 2 from Culex sitiens, one from Aedes species, and 3 from Culex species. Isolation of JE virus from Cx. sitiens, Cx. bitaeniorhynchus, and Aedes sp. (Aedes butleri and Ae. albopictus) is reported for the first time in Malaysia.